Verbal memory is associated with structural hippocampal changes in newly diagnosed Parkinson's disease. Issue 1 (15th November 2012) - Beyer, Mona K; Bronnick, Kolbjorn S; Hwang, Kristy S; Bergsland, Niels; Tysnes, Ole Bjorn; Larsen, Jan Petter; Thompson, Paul M; Somme, Johanne H; Apostolova, Liana G
Abstract : Background and objective: Cognitive impairment, including impairment of episodic memory, is frequently found in newly diagnosed Parkinson's disease (PD). In this longitudinal observational study we investigated whether performance in memory encoding, retention, recognition and free recall is associated with reduced hippocampal radial distance. Methods: We analysed baseline T1-weighted brain MRI data from 114 PD subjects without cognitive impairment, 29 PD subjects with mild cognitive impairment and 99 normal controls from the ParkWest study. Age- and education-predicted scores for the California Verbal Learning Test 2 (CVLT-2) and tests of executive function were regressed against hippocampal radial distance while adjusting for imaging centre. Results: There was no association between encoding or performance on executive tests and hippocampal atrophy in the PD group. In the full PD sample we found bilaterally significant associations between lower delayed free recall scores and hippocampal atrophy in the CA1, CA3 and subiculum area (left, p=0.0013; right, p=0.0082). CVLT-2 short delay free recall scores were associated with bilateral hippocampal CA1 and subicular atrophy in the full PD sample (left, p=0.013; right, p=0.047). CVLT-2 recognition scores showed a significant association with right-sided subicular and CA1 atrophy in the full PD sample (p=0.043). Conclusions: At the time of PD diagnosis, subjects' verbal memory performance in recall and recognition are associated with atrophy of the hippocampus, while encoding is not associated with hippocampal radial distance. We postulate that impaired recall and recognition might reflect deficient memory consolidation at least partly due to structural hippocampal changes.